A Comparative Study of Cross-Device Finger Vein Recognition Using Classical and Deep Learning Approaches - Tuğçe Arıcan; Raymond Veldhuis; Luuk Spreeuwers; Loïc Bergeron; Christoph Busch; Ehsaneddin Jalilian; Christof Kauba; Simon Kirchgasser; Sébastien Marcel; Bernhard Prommegger; Kiran Raja; Raghavendra Ramachandra; et al. (IET Biometrics)
Finger vein recognition is gaining popularity in the field of biometrics, yet the inter-operability of finger vein patterns has received limited attention. This study aims to fill this gap by introducing a cross-device finger vein dataset and evaluating the performance of finger vein recognition across devices using a classical method, a convolutional neural network, and our proposed patch-based convolutional auto-encoder (CAE). The findings emphasise the importance of standardisation of finger vein recognition, similar to that of fingerprints or irises, crucial for achieving inter-operability. Despite the inherent challenges of cross-device recognition, the proposed CAE architecture in this study demonstrates promising results in finger vein recognition, particularly in the context of cross-device comparisons.